Innovation and Overview of Technologies in the Open Educational Resources - Škraba, Andrej; Fetaji, Bekim; Zdravev, Zoran; Velinov, Aleksandar; Vavtar, Bojan; Lavrič, Franc (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This paper presents the collaborative efforts of researchers and educators from Albania, Croatia, Slovenia, and North Macedonia in updating a tutorial for Open Educational Resources (OER) as part of the Integrating Digital Content and Digitalization of High Schools (iDADOHS) project. Brainstorming sessions generated 46 ideas for enhancing OER tutorials, which were prioritized based on their potential impact. The focus was on digital content creation, interactive tools like GeoGebra, PhET, Kahoot, and Padlet, and an OER repository. Selected ideas shaped a comprehensive tutorial on Google Sites, providing technical guidance and innovative methodologies for classroom use. Advanced analysis techniques, including Latent Dirichlet Allocation (LDA) and Non-negative Matrix Factorization (NMF), categorized suggestions, ensuring a structured integration of digital tools. This initiative advances digital literacy and educational quality through collaborative, technology-driven solutions.